Is a bit more experience bad? The role of entrepreneurial experience on investment rate. Issue 6 (28th March 2019) - Nguyen, Bach
Abstract : Purpose: This study investigates the influence of entrepreneurial experience on small business investment. The purpose of this paper is to examine whether entrepreneurs with more prior start-up experience are better able to identify business opportunities and successfully transform these opportunities into investment projects. Design/methodology/approach: The empirical setting in this study is Vietnam. The authors employ a panel data of small businesses (mostly households) from 2005 to 2013, and use a fixed effect method to estimate the regression coefficients. The results are also re-checked using the general method of moments and matching technique. Findings: Empirically, it is found that entrepreneurial experience is an important determinant of investment decisions. Specifically, entrepreneurs with one start-up experience make more investments than novice entrepreneurs. However, entrepreneurs with more than one start-up experience do not make more investments than entrepreneurs with one start-up experience. Research limitations/implications: This is country-specific research. Further study may employ data from multi-countries to re-test the validity of the hypotheses. Originality/value: This study provides a new perspective for analysing the role of entrepreneurial experience on entrepreneurial investments. It shows that prior start-up experience may turn out to be a liability to entrepreneurs since it restricts their ability to identify new opportunities.